Penerapan Estimasi Skor Grup Domain untuk Meningkatkan Kualitas Pendidikan - Muhammad Tahir, Baharullah (Celebes Education Review, 2020)
The purpose of this study is to demonstrate the application of domain group score estimates in an effort to improve the quality of education, with Item Response Theory (IRT), using the Maximum Likelihood Estimation (MLE) method with item characteristics of one parameter logistic model (L1P), and using the xcalibre 4.2 software program . Based on the estimated results of the domain group score can be used to evaluate the success of the implementation of certain education, for a number of groups of certain education units for example based on the group of districts / cities in a province. Previously, education evaluation was only limited to student learning achievement, but by using domain group score estimation, in addition to evaluating student learning outcomes, students could also evaluate groups of students. The results of the domain group score estimation research can facilitate policy makers to determine appropriate actions in order to improve the quality of education. In this study the number of respondents used was 1000 students who were grouped into 20 groups, and each group consisted of 50 students. It was found that if the minimum score that is considered successful is 80, then there are still 7 groups of 20 groups of students who have not been successful because the scores are still below 80, namely groups: 9, 12, 13, 20, 7, 19, and 14.